Impact of a Major Inflow Event on the Composition and Distribution of Bacterioplankton Communities in the Baltic Sea - Bergen, Benjamin; Naumann, Michael; Herlemann, Daniel P. R.; Gräwe, Ulf; Labrenz, Matthias; Jürgens, Klaus (Frontiers in Marine Science, 2018)
Major Baltic inflow (MBI) events carry highly saline water from the North Sea to the central Baltic Sea and thereby affect both its environmental conditions and its biota. While bacterioplankton communities in the Baltic Sea are strongly structured by salinity, how MBIs impact the composition and distribution of bacteria is unknown. The exceptional MBI in 2014, which brought saline and oxygenated water into the basins of the central Baltic Sea, enabled the linkage of microbiological investigations to hydrographic and modelling studies of this MBI. Using sequence data of 16S ribosomal RNA (rRNA) and 16S rRNA genes (rDNA), we analyzed bacterioplankton community composition in the inflowing water and in the uplifted former bottom water at stations reached by the MBI. Bacterial diversity data were compared with respective data obtained from previous, non-inflow conditions. Changes in bacterial community composition following the 2014 MBI were mainly apparent at the genus level. A number of specific taxa were enriched in the inflowing water, with large changes in the rRNA/rDNA ratios indicating the different activity levels between of the water masses. The relative similarity of the bacterial communities in the inflowing and uplifted waters as well as the results from an inflow-simulating numerical model showed that the inflowing water did not originate directly from the North Sea but mostly from adjacent areas in the Baltic Sea. This suggested that the inflow event led to a series of shifts in Baltic Sea water masses among the Baltic Sea basins and a gradual mixing of the water bodies. Dramatic changes in the bacterial community composition occurred when the bottom-water inflow reached the anoxic, sulfidic deep basins, resulting in an uplifting of the formerly anoxic bacterial community, dominated by Epsilonproteobacteria. Our study of the impact of MBIs on bacterioplankton communities therefore highlights two relevant underlying mechanisms that impact the distribution and possibly also the activities of planktonic bacteria in the Baltic Sea: (1) the successive dilution of inflowing North Sea water with ambient waters and (2) the uplifting of former bottom-water communities to higher water strata.